Numerical simulation for entropy optimized nonlinear radiative flow of GO‐Al2O3 magneto nanomaterials with auto catalysis chemical reaction. Issue 3 (27th November 2020) - Shaw, Sachin; Mabood, Fazle; Muhammad, Taseer; Nayak, Manoj Kumar; Alghamdi, Metib
Abstract: Graphene oxide nanofluid is distinguished from other nanofluids due to its easy synthesis, longer suspension stability, higher thermal conductivity, lower erosion, corrosion, larger surface area and lower demand for pumping power‐favorable to some need of the industrial world. Entropy generation minimization is the best methodology to augment the rate of heat transportation. The infusion of both porous media and nanofluids can uplift the thermal efficiency of typical physical systems appositely. In view of such beneficiaries we intended to study the stagnation point flow of magnetized graphene oxide (GO) and alumina (Al2 O3 ) nanomaterials past a thin needle in the existence of a porous medium. The models for NLTR and HHRs are included for the greater scope of the problem. Extracted similarity ordinary differential equations are solved numerically by the bvp4c solver in MATLAB software. Mounting up porous matrix controls the viscous drag and HTR at the surface of thin needle. The dynamics between GO–water and Al2 O3 –water nanofluids over thin needle divulge that GO–water nanofluid accounts for appreciable controlled motion compared to Al2 O3 –water nanofluid. In addition, rising volume fraction and mounting up the porous matrix yields diminution of surface viscous drag and diminishing rate of heat transportation.